Erector Spinae Plane Block Versus Caudal Epidural Block in Pediatric Patients Undergoing Lower Limb Cancer Surgery - A Kotb, Tamer; Eltawab M Turki, Doaa Abd; Ghoniem , Ayman Ali; Bakeer, Ahmed Hussein; Gadalla, Youssef Ayad (Journal of Neonatal Surgery, 2025)
Caudal epidural block and Erector Spinae Plane Block (ESPB) are two regional anesthesia methods increasingly utilized in pediatric surgical patients. The caudal block is a well-established method involving the injection of local anesthetics into the epidural space via the sacral hiatus. Traditionally performed as a blind technique based on anatomical landmarks, it now benefits from image-guided methods like ultrasound, enhancing accuracy and safety. ESPB, a newer inter-fascial block introduced by Forero in 2016, involves depositing anesthetic between the erector spinae muscles and the transverse process. It enables cranio-caudal, lateral, and anterior spread of anesthetic across multiple vertebral levels, influencing various dermatomes depending on the site of injection. Anatomical differences between children and adults, including less developed bony structures and increased tissue compliance, influence the distribution of anesthetic in both techniques. While caudal blocks may encounter difficulty due to sacral anatomical variation, ESPB can be technically advantageous in children due to their thinner muscle layers and closer proximity of target structures to the skin. Both techniques require careful ultrasound guidance for optimal needle placement, particularly in complex or variable anatomy. This study focuses on comparing the anatomical and procedural characteristics of lumbar ESPB and caudal epidural blocks in pediatric lower limb oncologic surgeries, offering insight into their utility, feasibility, and anatomical considerations in this vulnerable population